2022
DOI: 10.1101/2022.02.09.479810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional GWAS of non-CG transposon methylation inArabidopsis thalianareveals major polymorphisms in five genes

Abstract: Genome-wide association studies (GWAS) have revealed that the striking natural variation for DNA CHH-methylation (mCHH; H is A, T, or C) of transposons has oligogenic architecture involving major alleles at a handful of known methylation regulators. Here we use a conditional GWAS approach to show that CHG-methylation (mCHG) has a similar genetic architecture - once mCHH is statistically controlled for. We identify five key trans-regulators that appear to modulate mCHG levels, and show that they interact with a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(167 reference statements)
1
1
0
Order By: Relevance
“…In the CHH context, our finding of a recurrent association at Chr5:10417744 (Figure 5b,e) confirms a recent study that identified natural alleles of CHROMOMETHYLASE2 (CMT2) as determinants of CHH methylation (Sasaki et al, 2019). Similarly, associations of transposon methylation in CHG context and the miR823 and MSI1 loci were recently reported (Sasaki et al, 2022). The association signal in CHH emerged from 120 DMRs, showing a general trend of lower methylation in accessions carrying the alternative allele, with the exception of two regions of overall low CHH methylation (Figure 5h).…”
Section: Methylscore Dmrs Reveal Recurrent Trans-acting Association S...supporting
confidence: 91%
“…In the CHH context, our finding of a recurrent association at Chr5:10417744 (Figure 5b,e) confirms a recent study that identified natural alleles of CHROMOMETHYLASE2 (CMT2) as determinants of CHH methylation (Sasaki et al, 2019). Similarly, associations of transposon methylation in CHG context and the miR823 and MSI1 loci were recently reported (Sasaki et al, 2022). The association signal in CHH emerged from 120 DMRs, showing a general trend of lower methylation in accessions carrying the alternative allele, with the exception of two regions of overall low CHH methylation (Figure 5h).…”
Section: Methylscore Dmrs Reveal Recurrent Trans-acting Association S...supporting
confidence: 91%
“…Natural accessions also vary substantially in their methylome, transcriptome, and mobilome (transposable element, TE) landscapes [14][15][16][17]. Largescale structural variation along with methylome variation at TEs is influenced by genetic variation at loci encoding components of the methylation machinery, suggesting that the methylation machinery is a target of selection during adaptation to the environment [15,16,[18][19][20][21]. Substantial variation in methylation is also apparent in genic regions, functioning as a storehouse of epialleles, some of which can impact key developmental processes and fitness under new environments [22,23].…”
mentioning
confidence: 99%